In Adult Horses With Septic Peritonitis, Does Peritoneal Lavage Combined With Antibiotic Therapy Compared to Antibiotic Therapy Alone Improve Survival Rates? - Sarah Scott Smith (Veterinary Evidence, 2017)
The quality of evidence in equids is insufficient to direct clinical practice aside from the following: The use of antiseptic solution to lavage the abdomen causes inflammation and is detrimental to the patient. For peritonitis caused by Actinobacillus equuli, treatment with antibiotics alone may be sufficient. A variety of antibiotics were used in the two reported studies.